Nature, politics, and the arts : essays on romantic culture in honor of Carl Woodring - De Almeida, Hermione, 1950- (University of Delaware Press, 2015)
Hermione de Almeida is Walter Professor Emerita of English and comparative literature at the University of Tulsa